2015
DOI: 10.1038/srep14923
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced regeneration and functional recovery after spinal root avulsion by manipulation of the proteoglycan receptor PTPσ

Abstract: Following root avulsion, spinal nerves are physically disconnected from the spinal cord. Severe motoneuron death and inefficient axon regeneration often result in devastating motor dysfunction. Newly formed axons need to extend through inhibitory scar tissue at the CNS-PNS transitional zone before entering into a pro-regenerative peripheral nerve trajectory. CSPGs are dominant suppressors in scar tissue and exert inhibition via neuronal receptors including PTPσ. Previously, a small peptide memetic of the PTPσ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 47 publications
4
35
0
Order By: Relevance
“…Recent studies show that administration of an RPTPσ cell-penetrating wedge peptide mimetic (ISP) promoted innervation and functional restoration in mice following spinal cord injury[65,66]. RPTPσ is a receptor for chondroitin sulphate proteoglycans (CSPGs), an abundant extracellular matrix (ECM) component in the scar tissue that is generated after CNS injury.…”
Section: Trends In Ptp-targeted Biologics Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that administration of an RPTPσ cell-penetrating wedge peptide mimetic (ISP) promoted innervation and functional restoration in mice following spinal cord injury[65,66]. RPTPσ is a receptor for chondroitin sulphate proteoglycans (CSPGs), an abundant extracellular matrix (ECM) component in the scar tissue that is generated after CNS injury.…”
Section: Trends In Ptp-targeted Biologics Developmentmentioning
confidence: 99%
“…ISP s.c. administration to rats following contusive spinal cord injury promoted axon regrowth within the CSPG-rich scar, restoring innervation to the spinal cord and recovery of locomotor and urinary systems[65]. ISP administration also improved motoneuron axon regeneration and motor function in rats subjected to spinal root avulsion injury, in which spinal nerves are disconnected from the spinal cord[66]. ISP administration also promoted cardiac innervation in a mouse model of myocardial infarction[67].…”
Section: Trends In Ptp-targeted Biologics Developmentmentioning
confidence: 99%
“…Administration of the PTPσ cell-penetrating wedge peptide mimetic inhibits PTPσ promoted innervation and functional restoration in mice following spinal cord injury. 271272 Treatment with the PTPσ cell-penetrating wedge peptide mimetic also promotes cardiac innervation in a mouse model of myocardial infarction. 273 Finally, in silico screening for compounds predicted to bind the interface between CD45’s D1 and D2 domains led to compound 211 (Figure 12).…”
Section: Therapeutic Targeting Of Ptp Regulatory Mechanismsmentioning
confidence: 99%
“…In animal models, the use of fibrin glue sometimes obviated surgical suturing (de Vries et al ., ). Our team found that directly reattaching the root back to the ventrolateral pia surface of the spinal cord can also achieve physical reconnection between the two stumps (Chai et al ., ; Gu et al ., ; Su et al ., ; Li et al ., ). Nevertheless, efficient axonal regeneration still requires exploring and integrity of other strategies to facilitate functional restoration.…”
Section: Discussionmentioning
confidence: 97%
“…At 6 weeks after surgery, needle EMG was performed by using an RM6240 multichannel signal process system (Chengdu Instrument Factory, Chengdu, China), as described previously (Li et al ., ). Two representative animals from each group were anesthetized by intraperitoneally injecting a mixture of ketamine (80 mg/kg of body weight) and xylazine (8 mg/kg body weight).…”
Section: Methodsmentioning
confidence: 97%